Flexural Performance of Laced Reinforced Concrete Beams under Static and Fatigue Loads (Journal of Engineering, 2019)
This paper introduces experimental results of eighteen simply supported reinforced concrete beams of cross sections ( ) and length 3000 mm to study the effect of lacing reinforcement on the performance of such beams under static and fatigue loads. Twelve reinforced concrete beams (two of them are casted with vertical shear reinforcement used as control beams) are tested under four points bending loading with displacement control technique and six laced reinforced concrete beams were exposed to high frequency (10 Hz) by fixing the fatigue load in each cycle. Three parameters are used in the designed beams, which are: lacing bar diameter (4mm, 6mm, and 8mm), lacing bar inclination angle to horizontal , and lacing steel ratio depending on number of lacing bar in each longitudinal face of beam and lacing bar diameter. The comparison results of experimental tests revealed that the ultimate loads of laced reinforced concrete beams are higher than the conventional reinforced concrete beams due to increasing lacing bar diameter, angle of inclination lacing bar, and lacing steel ratio, while the deflection is reduced. Also, the laced reinforced concrete beams can safely withstand the fatigue loading.